A REPORT OF RADIATION RISKS DURING AND AFTER PROCESSING MINERAL PLACER FROM SOUTHEAST AFRICA. Issue 1 (22nd April 2020) - Fu, Kan; Zou, Wei; Liu, Zhenzhou; He, Haiming
Abstract: Recently, high levels of radioactivity were found in products from Chinese mineral processing industries that handle mineral placer from Southeast Africa. The findings led to public panic. The aim of this work is to provide radiological data for the government, workers and the public. In this work, activity concentrations of 238 U, 232 Th, 226 Ra and 40 K in raw ore from Southeast Africa were analysed in the laboratory. Products like monazite and building material were analysed. High concentrations of 238 U, 232 Th and 226 Ra in products were found to be at a level of 10 4   Bq/kg. Around the South China Mineral Processing Industry, radioactivity in soil and groundwater was analysed. Absorbed dose rates in air and indoor radon concentrations at workplaces were monitored. Annual effective dose to workers and the public was calculated and found to exceed Chinese dose criterion. This report might be an alert for mining and mineral processing in Southeast Africa.